2010
DOI: 10.1007/s11427-010-0079-3
|View full text |Cite
|
Sign up to set email alerts
|

Medaka fish stem cells and their applications

Abstract: Stem cells are present in developing embryos and adult tissues of multicellular organisms. Owing to their unique features, stem cells provide excellent opportunities for experimental analyses of basic developmental processes such as pluripotency control and cell fate decision and for regenerative medicine by stem cell-based therapy. Stem cell cultures have been best studied in 3 vertebrate organisms. These are the mouse, human and a small laboratory fish called medaka. Specifically, medaka has given rise to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In 2006, Okutsu et al [85] developed a spermatogonial transplantation system of rainbow trout. In 2009, Yi et al [86,87] established haploid ES cell lines from medaka gynogenetic haploid embryos, and then created the semi-cloned female medaka which shows normal fertility by using the semi-cloning technology. Currently, most germ cells used for transplantation are derived from juvenile and adult males in a process that typically involves harvest of PGCs in spermatogonial stem cells or spermatogonia.…”
Section: Transplantation Of Germline Stem Cells and Germ Cellsmentioning
confidence: 99%
“…In 2006, Okutsu et al [85] developed a spermatogonial transplantation system of rainbow trout. In 2009, Yi et al [86,87] established haploid ES cell lines from medaka gynogenetic haploid embryos, and then created the semi-cloned female medaka which shows normal fertility by using the semi-cloning technology. Currently, most germ cells used for transplantation are derived from juvenile and adult males in a process that typically involves harvest of PGCs in spermatogonial stem cells or spermatogonia.…”
Section: Transplantation Of Germline Stem Cells and Germ Cellsmentioning
confidence: 99%
“…Moreover, some differentially expressed genes were identified from the cloned zebrafish embryos at the dome stage [37], and the critical developmental stages for high integration efficiency were determined in zebrafish [38,39]. Stem cell culture and application have been rapidly developed in model fishes of medaka and zebrafish [40,41], and some stem cell technologies, such as gene targeting, germ cell transplantation and semi-cloning by nuclear transfer, have been successfully formed because of specific potentials of fish germ stem cells and embryonic stem cells [42,43]. Especially, Yi et al [44] used the semi-cloning technology to create the semi-cloned female medaka which shows normal fertility and germline transmission over three generations.…”
Section: Somatic Cell Nuclear Transfer and Stem Cell Technologies In mentioning
confidence: 99%
“…Few fish stem cell lines have been obtained so far. An embryonic stem cell line from medaka has been established, which is stable and can differentiate into a variety of cell types to form chimeras of medaka embryos [111,112]. Chen et al [113] reported several embryonic stem cell lines from sea fishes with chimerical competence.…”
Section: Cell Engineering In Fish Reproductive Technologymentioning
confidence: 99%